Identification of a novel ATPase activity in 14‐3‐3 proteins – Evidence from enzyme kinetics, structure guided modeling and mutagenesis studies. Issue 1 (20th November 2013) - Ramteke, Manoj P.; Shelke, Pradnya; Ramamoorthy, Vidhya; Somavarapu, Arun Kumar; Gautam, Amit Kumar Singh; Nanaware, Padma P.; Karanam, Sudheer; Mukhopadhyay, Sami; Venkatraman, Prasanna
Abstract : 14‐3‐3 Proteins bind phosphorylated sequences in proteins and regulate multiple cellular functions. For the first time, we show that pure recombinant human 14‐3‐3 ζ, γ, ε and τ isofoms hydrolyze ATP with similar K m and k cat values. In sharp contrast the sigma isoform has no detectable activity. Docking studies identify two putative binding pockets in 14‐3‐3 zeta. Mutation of D124A in the amphipathic pocket enhances binding affinity and catalysis. Mutation of a critical Arg (R55A) at the dimer interface in zeta reduces binding and decreases catalysis. These experimental results coincide with a binding pose at the dimer interface. This newly identified function could be a moon lighting function in some of these isoforms. Abstract : Human 14‐3‐3 ζ, γ, ε, τ isoforms but not the sigma protein hydrolyze ATP. Activity was reduced in R55A 14‐3‐3ζ mutant. Activity was gained in D124A 14‐3‐3ζ mutant. Active isoforms show sequence/structure conservation.